Advances in Electrical Materials for Bone and Cartilage Regeneration: Developments, Challenges, and Perspectives - Yubin Yao; Xi Cui; Shenglong Ding; Ketao Wang; Mingzhu Zhang (Advanced Science, 2025)
Abstract Severe bone and cartilage defects caused by trauma are challenging to treat, often resulting in poor outcomes. An endogenous electric field (EnEF) is crucial for bone regeneration, making electrical materials a promising therapy. This review provides a comprehensive overview of the role of bioelectric signals in bone and cartilage cells, alongside recent advancements in electrical biomaterials, with particular emphasis on nanogenerators, piezoelectric materials, triboelectric scaffolds, and zwitterionic hydrogels. It further investigates the impact of these electrical biomaterials on bone and cartilage regeneration, as well as the applications of both endogenous and exogenous electrical stimulation (ES) and the mechanisms underlying ES‐induced cellular and molecular responses. Finally, the review underscores future directions for ES systems in tissue engineering, emphasizing the critical importance of integrating structural integrity, mechanical properties, and electrical signal delivery into intelligent implantable scaffolds.